The Correlation between Silence Phenomenon and EFL Student Online Class - Zahrah Qurota’ Ayu Nurrohmah; Alimin Adi Waloyo (English Learning Innovation (englie), 2021)
In order to eliminate the spread of the Corona Virus, the students have been being required to study from homes either synchronously or asynchronously. It is commonly known asan online class. It has been being done to cut the spread of theCOVID-19 virus. This new teaching approach needs EFL students to adjust their way of learning. Also, the online class creates some challenges, such as limited interaction, low motivation, internet connection issues, etc) for EFL learners in their learning process because teachers and students have less interaction. This situation is called a silence phenomenon. Due to this was a new type of issue in EFL teaching and less investigated research, the researchers conducted the study to investigate the factors and solutions of the silencing phenomenon faced by EFL students during an online class. This study employed a case study research method.The subjects of this studywere tenstudents of English Language EducationDepartment students, 2017 academicyear at the University of Muhammadiyah Malang (UMM). The researcher collected thedata through the interview technique.The interview was applied, so the researchers obtained rich and in-depth data. The finding of this studyshowed that students’active participation during online classes was very low.That low participation was caused by several aspects: individual, teacher,cultural, technological, and domestic. The students could implement various ways to minimize the students’ reticence in the online class. This research hopefully provides different views to make teachers' online classes fun and interesting, so English learning can obtain optimal outcomes.